KONTEKSTUALISASI PEMBELAJARAN SEJARAH MELALUI PERISTIWA BENCANA - Listyaputri, Dinar Rizky; Patridina, Esa P.B.G.G. (Sejarah dan Budaya: Jurnal Sejarah, Budaya, dan Pengajarannya, 2022)
AbstractThe challenges of learning history are increasingly diverse. One of the issues that often get repeated is regarding how irrelevant and out-of-context the history subjects are for students. According to the reason, designing a contextual history learning plays an important role. Learning history throughout the disaster events is an attempt to serve history, not only as part of human's past life but also as a widened field that is quite relevant to students' life. The fact that Indonesia is a disaster-prone country with a total of 763 natural disasters in the first quarter of 2021 is another reason that shows the urgency of learning disaster history. Bringing disaster events into history learning has a particular purpose of improving people's awareness of disaster hazards. This study used the literature studying method by analyzing every related reference. The purpose of this study is to find possibilities to design history learning through disaster events by analyzing the curriculum draft, collecting any sources about disaster histories, and concluding how it benefits students. Using environmental and disaster history as learning material is expected to be an inspiration for educators to develop and create a learning process that accommodates factual issues around students so that the subject does not lose its relevance.